2019
DOI: 10.1364/ol.44.004191
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced UV third-harmonic generation in microfibers by controlling nonlinear phase modulations

Abstract: The influence of nonlinear phase modulations on third harmonic conversion in silica microfibers is experimentally demonstrated. By utilizing such influence, enhanced narrow-bandwidth UV is generated at high signal-to-noise ratio (33 dB) and an average power of several hundred nanowatts. Detailed trends of third harmonic power against input pump power were characterized with peak pump power up to 2.5 kW, and the results agree with predicted features, confirming that harmonic output could be optimized with adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In 2003, Akimov et al demonstrated the THG in a 2.6-μm-diameter silica MNF using 30-fs 1250-nmwavelength pulses [70] . In the following 20 years, a series of theoretical and experimental studies have been carried out to optimize the conversion efficiency in nonlinear optical processes [71,[273][274][275][276][277][278][279][280] .…”
Section: Shg and Thgmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2003, Akimov et al demonstrated the THG in a 2.6-μm-diameter silica MNF using 30-fs 1250-nmwavelength pulses [70] . In the following 20 years, a series of theoretical and experimental studies have been carried out to optimize the conversion efficiency in nonlinear optical processes [71,[273][274][275][276][277][278][279][280] .…”
Section: Shg and Thgmentioning
confidence: 99%
“…In recent years, several effective approaches to realizing quasi-phase matching between the fundamental pump mode and the third-harmonic modes have been reported by Jiang et al . and Hao et al ., such as the employment of a counter-propagating pulse train [277] , nonlinear phase modulation [278,279] , and mechanical strain [280] . Indeed, the THG conversion efficiency excited by short laser pulses reported so far is basically on the order ranging from 107 to 104.…”
Section: Optical Waveguiding Properties Of the Mnfsmentioning
confidence: 99%